Cover Feature: Improvement of Anticancer Drug Release by Cobalt Ferrite Magnetic Nanoparticles through Combined pH and Temperature Responsive Technique (ChemPhysChem 21/2018). Issue 21 (11th October 2018) - Dey, Chaitali; Ghosh, Arup; Ahir, Manisha; Ghosh, Ajay; Goswami, Madhuri Mandal
Abstract : The Cover Feature illustrates the improved release of a cancer drug by functionalized cube‐shaped cobalt ferrite magnetic nanoparticles at a relative high pH 5.5 (the pH found in the cancer‐cell environment) and at an elevated temperature of 44 °C induced by an AC magnetic field. More information can be found in the Article by C. Dey et al. onpage 2872 in Issue 21, 2018 (DOI:10.1002/cphc.201800535 ).